ANALISIS KEBUTUHAN LAHAN PARKIR DI RUMAH SAKIT UMUM DAERAH - Messah, Yunita A.; Lay Kanny, Roky A.E.; Rizal, Andi Hidayat (Jurnal Teknik Sipil, 2012)
The regency hospital named Prof. Dr. W. Z. Johannes Kupang is located in Mochamad Hatta street. It is the one of central healthy service for Kupang society and surrounding. As the service central that most visited by public, the hospital has a problem that is the limited parking lot area. The problem makes a difficulty to the visitor to parking their vehicle because the parking is always full. Then, the visitor will parking their vehicle at the edge of Mochamad Hatta Street but it makes the traffic on the street. The method that used in this research is field survey. It is done by collecting data of observing the series number of cars and motorcycles that come in and out by the hospital. The data of research is analyzed by using regression analysis to know the influential variable of the space parkirng needed and based on the width of buildings floor. The result of the analysis is the corelation between the number of the medic and the parking needed of motorcycles which give the regression equivalent that fill the F test and t test, with the linear equivalent which is, Y = -3860.571 + 9.495 X3 and Y = -682.840 + 0.221 X1 – 0.207 X2 + 1.415 X3. By the equivalent, is known that the needed of motorcycle park is 498 partition and the needed of car park is 20 partition. Based on the parking needed and the parking width that space then know that the total space parking needed of motorcycle is 747 m2 with the parking sum is the 498 partition and the total space parking needed of car is 250 m2 with the parking sum is the 20 partition. The parking type of motorcycle that recommends is 90 degree and the parking type for car is 90 degree.